Planetary period magnetic field oscillations in Saturn's magnetosphere: Postequinox abrupt nonmonotonic transitions to northern system dominance. Issue 6 (21st June 2013) - Provan, G.; Cowley, S. W. H.; Sandhu, J.; Andrews, D. J.; Dougherty, M. K.
Abstract : [1] We examine the "planetary period" magnetic field oscillations observed in the "core" region of Saturn's magnetosphere (dipole L  ≤ 12), on 56 near‐equatorial Cassini periapsis passes that took place between vernal equinox in August 2009 and November 2012. Previous studies have shown that these consist of the sum of two oscillations related to the northern and southern polar regions having differing amplitudes and periods that had reached near‐equal amplitudes and near‐converged periods ~10.68 h in the interval to ~1 year after equinox. The present analysis shows that an interval of strongly differing behavior then began ~1.5 years after equinox, in which abrupt changes in properties took place at ~6‐ to 8‐month intervals, with three clear transitions occurring in February 2011, August 2011, and April 2012, respectively. These are characterized by large simultaneous changes in the amplitudes of the two systems, together with small changes in period about otherwise near‐constant values of ~10.63 h for the northern system and ~10.69 h for the southern (thus, not reversed postequinox) and on occasion jumps in phase. The first transition produced a resumption of strong southern system dominance unexpected under northern spring conditions, while the second introduced comparably strong northern system dominance for the first time in these data. The third resulted in suppression of all core oscillations followed by re‐emergence of both systems on a time scale of ~85 days, with the northern system remaining dominant but not as strongly as before. This behavior poses interesting questions for presently proposed theoretical scenarios. Key Points: New rotation period phenomena at Saturn are studied using magnetic field data Several abrupt changes in amplitudes and periods of both N and S oscillations Unexpected interval of S system dominance, followed by interval of N dominance.